The human rights-based approach to carbon finance / Damilola S. Olawuyi. - Olawuyi, Damilola S. (Damilola Sunday), 1983- (Cambridge University Press, 2016)
This book analyses the topical and contentious issue of the human rights impacts associated with carbon projects, especially in developing countries. It outlines a human rights-based approach to carbon finance as a functional framework for mainstreaming human rights into the design, approval, finance and implementation of carbon projects. It also describes the nature and scope of carbon projects, the available legal options for their financing and the key human rights issues at stake in their planning and execution. Written in a user-friendly style, the proposal for a rights-based due diligence framework through which human rights issues can be anticipated and addressed makes this book relevant to all stakeholders in carbon, energy, and environmental investments and projects.